Alternatif Pembelajaran Aktif di Era Pandemi melalui Metode Pembelajaran Game Based Learning - Muhammad Ari Kusuma; Djoko Dwi Kusumajanto; Rima Handayani; Indra Febrianto (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2022)
This article aims to see how the use of digital technology through game-based learning methods is effective in the COVID-19 pandemic era by using interesting learning so that students who are learning remain active. This type of research is literature review research using literature study that utilizes literature as the primary object in research. By utilizing technology in learning using game-based learning methods, it can provide more active, interesting, effective and efficient learning during the COVID-19 pandemic.